Rancang Bangun Sistem Informasi STIKOM PGRI Banyuwangi Berbasis Website - Layinatul Ummah; Faruk Alfiyan (Jurnal Informatika dan Komputer, 2026)
STIKOM PGRI Banyuwangi is an academic institution focused on information technology and computer science, making a modern, responsive, and functional web-based information system essential. The current system is considered less effective in terms of user interface design and ease of information access for the academic community. Therefore, this study aims to design and develop a more structured, interactive, and user-oriented web-based information system tailored to the campus’s needs. The selection of STIKOM PGRI Banyuwangi as the research object is based on the relevance of its need for improved web-based systems.This study adopts the prototype method to facilitate the iterative process of designing, testing, and evaluating the system, allowing users to provide direct feedback during development. The system is built using PHP for the back-end, supported by front-end technologies such as HTML and CSS, to produce a dynamic, flexible, and scalable web application. The final objective of this research is to create a campus information system that provides a more intuitive interface, faster access to essential features such as news, announcements, and suggestion forms, and a responsive design that functions well across various devices.